Students’ engagement through technology and cooperative learning: a systematic literature review - Aliyu, Jaafaru (Macrothink Institute, 2022)
Students’ engagement (SE) is an inherent part of learners’ participation in a classroom instructional task through different and diverse activity-based media. This paper analyses a logical literature of SE with cooperative learning (CL) and technology integration (TI). The outcomes reveal the impact of instructional methodology such as active learning through cohort instructions to generate conceptual understanding and SE, critical thinking, and student-centred activities, blended and flipped learning, Google Docs (a free Web-based tool that allows you to create, edit, and store documents online), and massive open online course (MOOC) to improve student homework. The systematic review of the literature establishes outcomes from current research conducted between January 2013 and June 2022. Out of 114 papers, thirty publications fulfilled the refining and exclusion/inclusion guidelines after standard evaluation screening of the journals and review, along with the additional elimination of repetitive records from the study. The goal of the evaluation is to analyse the effectiveness of all the papers utilised in the research. The literature review possibilities are illustrated by the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework. The limitations and discussion from this systematic literature review (SLR) address some gaps, future directions for SE, and implications for education and research.